If Sick-Leave Becomes More Costly, Will I Go Back to Work? Could It Be Too Soon? - Olivier Marie; Judit Vall-Castello (Institute of Labor Economics (IZA), 2020)
We investigate the impact on work absence of a massive reduction in paid sick leave benefits. We exploit a policy change that only affected public sector workers in Spain and compare changes in the number and length of spells they take relative to unaffected private sector workers. Our results highlight a large drop in frequency mostly offset by increases in average duration. Overall, the policy did reduce number of days lost to sick leave. For some, however, return to work may have been premature as we document huge increases in both the proportion of relapses and working accidents rates.
Keywords: I12; I13; I18; J22; J28; J32; 330; sickness insurance; paid sick leave; absenteeism; presenteeism; relapses contagious diseases; benefit displacement; working accidents; negative externalities; Spain; COVID-19